Acerola by-product as a renewable source of bioactive compounds: arabic gum and maltodextrin nanocapsules - CARNEIRO,Alessandra Pinheiro de Góes (2020)
Abstract Acerola industrial by-products present high levels of antioxidant compounds. Encapsulation technology has shown to be of great importance in the food industry. In this context, better nanoparticles are indicated in aiming to enrich food products with bioactive compounds. Five formulations were analyzed for yield, size distribution and zeta potential, infrared spectroscopy, encapsulation efficiency and doping. The yield data presented values from 38.01% to 44.34%. The nanoparticles had sizes varying from 27.12 nm to 308.80 nm and negatively charged surfaces. The encapsulation efficiency was quantified based on the vitamin C content, total extractable polyphenols and antioxidant activity according to specific methodology taking into account the different compounds ranging from 25.44% to 69.37%; 66.45% to 99.56% and 2.24% to 6.54%, respectively. The above data indicate that nanoparticles made with acerola by-products and arabic gum/maltodextrin are promising as natural food additives, with high levels of bioactive compounds.